2006
DOI: 10.1152/ajpregu.00618.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-level-sensitive sodium channel Nax is expressed in glial laminate processes in the sensory circumventricular organs

Abstract: Na(x) is an atypical sodium channel that is assumed to be a descendant of the voltage-gated sodium channel family. Our recent studies on the Na(x)-gene-targeting mouse revealed that Na(x) channel is localized to the circumventricular organs (CVOs), the central loci for the salt and water homeostasis in mammals, where the Na(x) channel serves as a sodium-level sensor of the body fluid. To understand the cellular mechanism by which the information sensed by Na(x) channels is transferred to the activity of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 27 publications
(45 reference statements)
6
82
0
Order By: Relevance
“…I.2A; Goldin et al, 2000). elevations in body fluids within the physiological range (Hiyama et al, 2002;Noda and Hiyama, 2005;Noda, 2006;Watanabe et al, 2006;Noda and Sakuta, 2013;Noda and Hiyama, 2015a;Noda and Hiyama, 2015b). The sensitivity of Na x to [Na + ] was revealed to be upregulated by endothelin-3 through activation of endothelin receptor B (Hiyama et al, 2013).…”
Section: Na X Channel Modulates Salt Appetite According To the Body-fmentioning
confidence: 99%
“…I.2A; Goldin et al, 2000). elevations in body fluids within the physiological range (Hiyama et al, 2002;Noda and Hiyama, 2005;Noda, 2006;Watanabe et al, 2006;Noda and Sakuta, 2013;Noda and Hiyama, 2015a;Noda and Hiyama, 2015b). The sensitivity of Na x to [Na + ] was revealed to be upregulated by endothelin-3 through activation of endothelin receptor B (Hiyama et al, 2013).…”
Section: Na X Channel Modulates Salt Appetite According To the Body-fmentioning
confidence: 99%
“…Other genes that are expressed in glial cells are related to water and ion homeostasis (Simard and Nedergaard, 2004). A gene that was persistently upregulated was the Scn6a, an atypical sodium channel gene that serves as a sodium-level sensor of the body fluid (Hiyama et al, 2002;Watanabe et al, 2006). This gene was originally considered to be a glial sodium channel (Gautron et al, 1992), although neuronal localization has also been observed (Grob et al, 2004).…”
Section: Glia and Ion Homeostasismentioning
confidence: 99%
“…The existence of specific cerebral Na ϩ sensors for the detection and correction of hydromineral imbalance has long been hypothesized (Andersson et al 1975;Cox et al 1987;Olsson and Kolmodin 1974;Weisinger et al 1979), and a concentration-sensitive Na ϩ channel, called the Na X channel, has been reported to control sodium ingestion in mice (Noda 2006;Watanabe et al 2000). In these rodents, the Na X channel is specifically expressed by glial cells of the circumventricular organs (Watanabe et al 2006). In addition, the transduction of the ECF [Na ϩ ] (Ͼ150 mM) into neuronal action potentials involves a complex mechanism and results in part from lactate release by glial cells under hypernatriuric conditions (Shimizu et al 2007).…”
Section: Introductionmentioning
confidence: 99%